Penerapan Six Sigma Dalam Pengendalian Kualitas Produk Mebel Pada PT Alis Jaya Ciptatama - Galih Adi Wibowo; Ari Zaqi Al Faritsy (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
The obstacle faced by PT Alis Jaya Ciptatama is that the production process carried out in 2022 still has many product defects. For this reason, it is necessary to improve the quality of the product. In this case the method used is the Six Sigma method as a quality improvement tool. The results of analysis using Pareto diagrams obtained the highest type of defect with a percentage of 38.2%, and there are three elements that influence this type of defect, namely human, machine and material elements. Through DMAI analysis, the company's average sigma value of 2.70 is still far from the company's expectations of 6, with a Defect Por Million Opportunities (DPMO) of 115362.894. This value is the most critical failure mode so it needs to be repaired. The proposed improvement is by implementing 5S and providing Standard Operating Procedures (SOP) so that operators work in accordance with operational standards in the mill 1 work area. Then a comparison is made between before and having been given the SOP, so the DPMO value is 72,666 and the sigma value is increased by 0.53.